Modulation of copper homeostasis and cuproptosis by PDHA1 in acute myeloid leukemia - Tianping Chen; Nan Wei; Wenxiu Lv; Lijun Qu; Qian Qu; Chaohong Wu; Yuan Ling; Haipeng Liu; Hongjun Liu (Discover Oncology)
Abstract Background Acute myeloid leukemia (AML) is an aggressive malignancy with poor prognosis. Recent studies highlight cuproptosis, a copper-dependent cell death mechanism, as a potential therapeutic target in cancers. This study investigates the expression and functional significance of CRGs, particularly PDHA1, in AML progression and cuproptosis regulation Methods We integrated bioinformatics analysis and experimental validation. Bioinformatics analysis of RNA-seq data from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) was performed to identify CRGs associated with AML. Among these, pyruvate dehydrogenase E1 alpha subunit (PDHA1) was selected for further investigation. AML cell lines (Kasumi-1, U937, etc.) were treated with Elesclomol-CuCl2 to induce cuproptosis. PDHA1 was overexpressed via transfection, and its effects on proliferation (CCK-8, spheroid formation), apoptosis (flow cytometry), cell cycle (propidium iodide staining), and copper ion content were assessed. qPCR, Western blot, and glutathione (GSH) assays evaluated gene/protein expression and redox status. Results Our analysis revealed that PDHA1 is significantly downregulated in AML tissues compared to normal controls. Overexpression of PDHA1 in AML cell lines led to reduced cell proliferation, increased apoptosis, and G1 phase arrest. Additionally, PDHA1 overexpression was associated with downregulation of Cyclins D1 and D3. Importantly, PDHA1 overexpression enhanced the sensitivity of AML cells to copper-induced cytotoxicity, indicating its potential to modulate cuproptosis. Conclusion These findings suggest that PDHA1 regulates cuproptosis by modulating copper metabolism and may serve as a potential therapeutic target and biomarker in AML.